Is Population Growth a Requisite for National Economic Growth? A Revisit of the Debate Using Panel Data Analysis - Onogiese, Osobase Anthony; Friday, Ohioze Wilson; Musa, Samuel Olayinka; OJO, Tope Joshua; Olufolake, Charles Ayobola (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 4, 2022)
This current paper reassesses the controversial discourse regarding the impact of population growth on national economies using data from 66 countries that constitute 85 per cent of the global population. The panel data spans through the periods 2001-2019. The variables include GDP per capita (regressand), aggregate population, fertility rate, life expectancy, crude death rate and gross fixed capital formation. The fixed effects estimator and panel causality tests were utilized to estimate the data. Findings from the fixed effects model suggests that GDP per capita is adversely and significantly predicted by the aggregate population and fertility rate whereas, gross fixed capital formation and crude death rate exert a positive significant effect on the regressand. Surprisingly, the panel causality result advances that there is a two-way causality between the regressand and the regressors. Following the findings, it is recommended that pragmatic policy measures that will control the rising fertility rate, encourage skill acquisition programs and raise employment generation for the rising population will be a welcome development.